Inflammation-Induced Increase in Evoked Calcium Transients in Subpopulations of Rat DRG Neurons - Lu, Shao-Gang (2008)
The concentration of intracellular Ca(2+) ([Ca(2+)](i)) influences neuronal properties ranging from excitability to neurotransmitter release. Persistent inflammation is associated with changes in the properties of primary afferent neurons ranging from excitability to transmitter release. The purpose of the present study was to determine whether previously described inflammation-induced changes in excitability and transmitter release are associated with changes in the regulation of [Ca(2+)](i). Acutely dissociated dorsal root ganglion (DRG) neurons harvested from adult rats 3 days following a hindpaw injection of complete Freund’s adjuvant (CFA) or naïve controls, were stimulated with 30 mM K(+) (Hi K(+)). Hi K(+) evoked changes in [Ca(2+)](i) were assessed with fura-2 ratiometric microfluorimetry. Subpopulations of DRG neurons were defined by cell body diameter, IB4 binding, capsaicin (CAP) sensitivity and target of innervation (DiI labeling). Inflammation was associated with significant increases in resting [Ca(2+)](i) and increases in the magnitude and decreases in the decay, of the evoked increase in [Ca(2+)](i). The changes in evoked transients were larger in neurons innervating the site of inflammation. Furthermore, there were differences among subpopulations of DRG neurons with respect to changes in magnitude and/or decay of the evoked transient such that the increase in magnitude was larger in small- and medium-diameter neurons than in large diameter neurons while the decrease in the decay was greater in CAP responsive, IB4 positive, small- and medium-diameter neurons than in CAP unresponsive, IB4 negative and/or large-diameter neurons. These changes in the regulation of [Ca(2+)](i) were not due to inflammation-induced changes in passive or active electrophysiological properties. Importantly, an inflammation-induced increase in evoked Ca(2+) transients in putative nociceptive afferents may contribute to the pain and hyperalgesia associated with persistent inflammation via facilitation of transmitter release from these afferents.